Pengaruh Pembelajaran IPS Berbasis Masalah dengan Strategi Think Talk Write (TTW) terhadap Kemampuan Kognitif dan Keaktifan Siswa Kelas VIII SMPN 3 Srengat Kabupaten Blitar - Sofi Ayu Nur Martasari; Nur Isroatul Khusna (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2025)
This research is based on the condition of students who are less enthusiastic and tend to be passive during learning. Students consider social studies to be boring and difficult, resulting in low student activeness. This low activeness affects students’ cognitive abilities. An effort that can be made is to create a fun learning atmosphere by using appropriate and interesting learning strategies, one of which is the Think Talk Write learning strategy. This strategy makes students active and more enthusiastic, so they achieve satisfying cognitive ability scores. The problem formulation in this research is how much influence the Think Talk Write strategy has on cognitive abilities, student activeness, and both in social studies subjects. This research uses a quantitative approach with a Quasy Experimental Design and a nonequivalent control group design. The sample consists of 29 students in the control class and 26 students in the experimental class. The sampling technique used is purposive sampling, with data collected through cognitive ability tests and student activeness sheets. Data analysis was performed using the Independent Sample T-Test and MANOVA. The results show that the Think Talk Write strategy influences students’ cognitive abilities and activeness, with a significance value of 0.000 < 0.05.